The Role Of The Medical Committee In Improving The Quality Of Health Services Ar Dr. Pringadi Hospital Medan City - Helga Kurniawati Tandungan; Ermi Girsang; Irza Haicha Pratama (Jurnal Ners, 2025)
This study aims to analyze the role of the Medical Committee in improving the quality of health services at Dr. Pirngadi Hospital, Medan City. The Medical Committee plays an important role in maintaining the professionalism of medical personnel and ensuring quality medical services through medical audits, continuing education, scientific meetings, and mentoring new medical personnel. Using a qualitative descriptive method with an in-depth interview approach to informants consisting of medical staff, doctors, patients, and nurses. This study shows that the role of the Medical Committee at Dr. Pirngadi Hospital has been carried out well, especially in medical audits, although there are obstacles in implementing follow-up audit results due to limited time and facilities. The role of the Medical Committee in organizing scientific meetings and continuing education is still limited and not made a routine program, while the mentoring process (proctoring) for new medical personnel has not been well structured. Through this study, it is clear that although the Medical Committee has played a role in improving the quality of services through medical audits, there is still room for improvement, especially in terms of continuing education and proctoring new medical personnel.